Physical properties and moisture retention characteristics of some Nigerian soils - Lal, R. (Elsevier, 1978)
Measurements were made of physical characteristics of 119 samples from 23 profiles derived from two parent materials in Nigeria. The laboratory analyses included texture, plasticity and shrinkage characteristics, and a range of soil moisture constants including saturation point and moisture retention at various suctions. Simple and multiple correlation coefficients and regression analyses were conducted to investigate the possibilities of obtaining estimates of soil moisture retention from the textural analysis. Clay and sand contents are correlated with various soil moisture constants. The textural analysis may therefore be used to estimate moisture holding capacity at different suctions for these and similar soils with a predominantly uniform clay mineralogy, dominated by kaolinite and sesquioxides. Moisture retention curves indicate that the “field capacity” for most of these soils is better estimated at 60 or 100 cm of water suction rather than at 0.3 bar. A plot of the pF curves indicated only slight differences between moisture retention at 2 or 3 bar suction and at 15 bar suction.